The prognostic significance of hematological parameters in women with uterine serous papillary carcinoma (USPC). (April 2016) - Younes, Grace; Segev, Yakir; Begal, Julia; Auslender, Ron; Goldberg, Yael; Amit, Amnon; Lavie, Ofer
Abstract: Objectives: Preoperative hematologic parameters: thrombocytosis, leukocytosis and anemia have been demonstrated to be independent poor prognostic factors in ovarian and endometrial cancers. However, little is known about their relation to uterine serous papillary carcinoma (USPC). We evaluated several preoperative hematologic parameters and their association with clinicopathologic features, disease progression and overall survival in USPC patients. Study design: This was a retrospective cohort study reviewing charts of all patients with a histologic pure USPC at two gynecologic oncology centers from January 2000 through July 2012. All patients had comprehensive hematologic tests prior to primary surgical treatment and were exposed to the same adjuvant treatment protocol. Results: The study included 56 patients, mean age at diagnosis 69.4 ± 15. Six (11%) had platelet count above 400000 10 6 /L, of them four (66%) were dead at the end of follow up (HR = 1.4, p = 0.48; CI 95% 0.5−4.3). The mean hemoglobin level was 12.3 g/dl, fibrinogen 437.5 mg/dL and lymphocytes 2013/μL. None of these parameters was significantly associated with 5 year survival. Leukocyte and neutrophil levels were adversely associated with survival. Of 15 patients with leukocytosis >10000/μL, 67% were dead at the end of follow up (HR = 3.98, p = 0.003; CI 95% 1.6−9.8). Of the 27 with neutrophils above 65%, 14 (52%) were dead at the end of follow up (HR = 3.1; p = 0.015; CI 95% 1.2−7.8). Conclusions: In patients with USPC, leukocytosis and neutrophilia are associated with aggressive tumor biology, and may predict a lower 5 year survival.